2022
DOI: 10.3390/ma15124364
|View full text |Cite
|
Sign up to set email alerts
|

About Inverse Laplace Transform of a Dynamic Viscosity Function

Abstract: A dynamic viscosity function plays an important role in water hammer modeling. It is responsible for dispersion and decay of pressure and velocity histories. In this paper, a novel method for inverse Laplace transform of this complicated function being the square root of the ratio of Bessel functions of zero and second order is presented. The obtained time domain solutions are dependent on infinite exponential series and Calogero–Ahmed summation formulas. Both of these functions are based on zeros of Bessel fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Finding a generalization of the modified Calogero-Ahmed series began with the need to find the two solutions in the original works of Calogero and Ahmed [21][22][23] that are missing there. These solutions were necessary to develop the formula (4) in the paper [20]. During our research it has been noticed that for the modified Calogero-Ahmed series the following recursive formula has been derived:…”
Section: Generalization Of Modified Calogero-ahmed Summation Formulasmentioning
confidence: 99%
See 3 more Smart Citations
“…Finding a generalization of the modified Calogero-Ahmed series began with the need to find the two solutions in the original works of Calogero and Ahmed [21][22][23] that are missing there. These solutions were necessary to develop the formula (4) in the paper [20]. During our research it has been noticed that for the modified Calogero-Ahmed series the following recursive formula has been derived:…”
Section: Generalization Of Modified Calogero-ahmed Summation Formulasmentioning
confidence: 99%
“…Recent research on the inverse of the function describing the dynamic viscosity function 𝕄 to the time domain [20] revealed that the solution in the time domain can be presented as an infinite series of exponential functions based on zeros of the Bessel function:…”
Section: Calogero-ahmed Summation Formulasmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercially available commercial FEM calculation packages allow for simple linear analyses, as well as complex calculations involving geometrically and physically non-linear issues [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. It is also worth mentioning that this study involved using the popular finite element method, which is widely used in many fields [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%